MENINGKATKAN HASIL BELAJAR LEMPAR CAKRAM DENGAN MENGGUNAKAN MODEL AKTIVITAS SIRKUIT PADA SISWA KELAS VIII B SMP NEGERI 10 SURAKARTA TAHUN PELAJARAN 2012/2013 - Supriyanto, Supriyanto (Jurnal Phederal Penjas, 2013)
The objective of research is to improve the discus learning achievement of the VIII B graders of SMP Negeri 10 Surakarta in the school year of 2012/2013 using circuit activity model.This study was a classroom action research. The research was conducted in two cycles, each of which consisted of planning, acting, observing, and reflecting. The subject of research was the VIII B graders of SMP Negeri 10 Surakarta in the school year of 2012/2013 consisting of 28 students: 14 males and 14 females. The data source derived from teachers and students. Techniques of collecting data used were discus ability test and measurement, and observation on the learning activity process. The data analysis was done using descriptive technique based on the qualitative analysis.The result of research showed that the use of circuit activity model could improve the students? discus learning achievement from pre-cycle to cycle one and from cycle one to cycle two. From the result of analysis obtained, the improvement of cycle one in passing category was 60.74%, with the 17 students passing successfully. In the second cycle, there was an increase of percentage passing of 85.74% with 24 students passing successfully.The conclusion of research was that the use of circuit activity model could improve the discus learning achievement in physical education learning of the VIII B graders of SMP Negeri 10 Surakarta in the school year of 2012/2013.Keywords: discuss learning achievement, circuit activity learning model